Question #829b0

2 Answers
Feb 1, 2018

Given ln(5x-3y^2), d/dx[ln(5x-3y^2)]=(5-6y)/(5x-3y^2)

Explanation:

ln(5x-3y^2)
First, you derive the inside of the function (5x-3y^2)
1. 5-6y
Second, you put this answer over the inside of the function.
2. d/dx[ln(5x-3y^2)]=(5-6y)/(5x-3y^2).

Feb 1, 2018

Please see below.

Explanation:

.

Let u=5x-3y^2

du=5dx-6ydy

d(ln(5x-3y^2))=d(lnu)=1/udu=(5dx-6ydy)/(5x-3y^2)

If we only differentiate with respect to x we will have:

(du)/dx=5

d/dx(ln(5x-3y^2))=d/dx(lnu)= 1/udu=5/(5x-3y^2)